2006
DOI: 10.1029/2005jc003250
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling off Yangtze River estuary in summer

Abstract: [1] The mechanisms of upwelling off the Yangtze River estuary (YRE) and in the adjacent waters in boreal summer are studied using numerical modeling. First, the persistent feature of this phenomenon is confirmed using cruise observations, satellite sea surface temperature (SST), and SST climatologic data. Then, the MASNUM (Marine Science and Numerical Modeling) wave-tide-circulation coupled numerical model is employed to simulate the upwelling patterns. On the basis of the simulation, a set of numerical experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 27 publications
(40 reference statements)
5
98
1
Order By: Relevance
“…From the SST distribution, we found a strong cold water tongue appearing off Hangzhou Bay. Another low SST center was situated at 122-124 • E, 33 • N, near Jiangsu coast, which was consistent with the results reported by Lü et al (2006). The low-temperature region in surface layer water was usually an effective index for identifying the upwelling.…”
Section: Model Validationsupporting
confidence: 80%
“…From the SST distribution, we found a strong cold water tongue appearing off Hangzhou Bay. Another low SST center was situated at 122-124 • E, 33 • N, near Jiangsu coast, which was consistent with the results reported by Lü et al (2006). The low-temperature region in surface layer water was usually an effective index for identifying the upwelling.…”
Section: Model Validationsupporting
confidence: 80%
“…In fact, a large part of the global deep ocean has vertical mixing in the order of 0.1 cm 2 s −1 . The wave-circulation coupled model has shown satisfactory performances in a series of circulation modeling studies in the Yellow Sea and East China Sea (Qiao et al 2004bLü et al 2006;Xia et al 2006). Preliminary results even indicate that the wave-induced mixing can improve a common problem in climate models known as the "too cold tongue" in the tropical Pacific (Song et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Fronts normally form natural barriers to the water transport (Wolanski and Hammer 1988) and, thus, decrease the horizontal and in turn vertical transport of the upwelled water masses. It has been shown that frontal zones could also be regions where the deep water is upwelled into the surface layer (Savidge 1976;James 1978;Lü et al 2006). Nevertheless, the generation of the front under the post-storm stage off the northeastern Hainan coast is a temporary phenomenon, which is gradually developing, and thus does not support the prerequisite condition of a frontal induced upwelling.…”
Section: Thermocline Variation At Different Wind Stagesmentioning
confidence: 99%